Development of measurement system using online software for shear-horizontal surface acoustic wave sensor. (24th March 2021) - Maekawa, Naoki; Kondoh, Jun
Abstract: In the medical field, point-of-care testing (POCT) is garnering attention. An online inspection system can be realized by combining POCT and the Internet. Herein, we report the performances of a measurement system developed using online software for a shear horizontal surface acoustic wave (SH-SAW) sensor. The developed SH-SAW measurement system does not require a phase detection circuit. The developed system can be used when the system is connected to the Internet. This enables an online measurement system that can be used "by anyone, at anytime, and anywhere." In this study, we used samples of glycerol and water mixtures and then measured the amplitude ratio and phase difference of the SH-SAW sensor. The validity of the developed system is confirmed by comparing the measured results with theoretical values.